PROFESSIONAL COMPETENCE OF ACCOUNTANTS IN UKRAINE: HOW TO CHECK? (Economic journal of Lesya Ukrainka Volyn National University, 2022)
Introduction. The competence of accountants affects not only the efficiency of an individual enterprise. This is a socially significant profession on which the formation of information for decision-making at the state level also depends. In Ukraine, there is a mandatory certification of auditing and accountants of financial institutions. The competence of the accountants of ordinary enterprises is not monitored in any way. It is important to study the competence of accountants to substantiate the importance of professional development of accountants at the state level.Purpose of the article. The aim of the study is to assess the competence of chief accountants in Ukraine by confirming or refuting two hypotheses. First: the professional experience of an accountant has a positive effect on the professional competence of an accountant, and therefore on the state of accounting; to assess competence, one can focus on professional work experience. Second, large enterprises employ more competent chief accountants, as the work requires more knowledge and training.Results. Both hypotheses were confirmed with the only remark that the indicators of accountants with more than 41 years of experience sharply deteriorate. The research results are based on the assessment of the competence of the main accountants of joint stock companies. The assessment was carried out using the indicator “the number of negative results of tax audits and court cases with regulatory authorities”. Analyzed the dependence of the indicator on the professional experience of the accountant, the size of the enterprise, the presence of foreign owners in the structure of the authorized capital. The source of data for the analysis was the reporting of 334 joint-stock companies of Ukraine, which are required to disclose data on the education, experience, age of the chief accountant. These data were supplemented with information from the STS database and the Register of court decisions. It was found that the analyzed indicator in micro and outsourcing enterprises is the worst.Conclusions. The above research results prove the need for the introduction of domestic certification, advanced training with an optimal budget to ensure the quality of accounting information.
Keywords: accountant, accountant's competence, results of tax audits, outsourcing, joint-stock company.